In Vitro Effect of Acidic Challenges on the Physical Properties of Dental Prosthesis Artificial Teeth - Laísa Daniel Gondim; Taís Chaves Magalhães; Alana Gail Lopes; Marjorie Izabella Batista Aguiar; Hugo Lemes Carlo; Tais de Souza Barbosa; Fabíola Galbiatti de Carvalho (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the effect of immersion and acid challenge with cola drink on color change (ΔE), Vickers hardness (VHN) and surface roughness (Ra) of artificial acrylic resin teeth. Material and Methods: The artificial teeth were divided into 6 groups (n= 8): TC (Trilux/Control), BC (Biotone/Control), TAC (Trilux/Acid challenge), BAC (Biotone/Acid challenge), TI (Trilux/Immersion) and BI (Biotone/Immersion). The teeth were embedded in acrylic resin and the labial side was serially polished to provide appropriate flat surface. The samples of TC, BC, TI, BI groups were immersed in artificial saliva and cola drink (coke) for 7 days, respectively. The acid challenge was performed with immersion of samples in coke for 5 min, and subsequently immersion in artificial saliva for 2h. This cycle was repeated at 4 times/day, during 7 days. The tests of VHN, ΔE and Ra were analyzed before and after the challenge and immersion groups. Data was analyzed by ANOVA, Tukey and T test (α = 0.05). Results: There was no difference in Ra values between groups after treatments. However, there was a decrease in VHN for all groups. BI (19.2 ± 0.3) presented significantly lower hardness than BAC (19.5 ± 0.9) and BC (20.2 ± 0.5). Groups BI (2.18 ± 0.41) and TI (1.50 ± 0.43) had statistically higher ΔE compared to the other groups. Conclusion: The hardness of resin teeth decreased after acid challenges, but the roughness surface was not affected. The color was more affected by the times of exposure in cola beverage and remineralization in artificial saliva, which were associated to the material degradation.